2005
DOI: 10.1086/427110
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Spectrum of Pulmonary Involvement in Leptospirosis in a Region of Endemicity, with Quantification of Leptospiral Burden

Abstract: Of 633 consecutively enrolled febrile patients, 321 (50.7%) had antileptospiral IgM antibodies or high titers of antileptospiral antibodies. Seven patients with histories of only urban exposure to leptospires had severe pulmonary manifestations; of these, 5 patients died; 4 of the deaths were caused by pulmonary hemorrhage, and 1 was caused by acute respiratory distress syndrome and multiorgan failure. Real-time, quantitative PCR assay showed high levels of leptospiremia (>or=10(4) leptospires/mL) in most fata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
149
1
13

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(168 citation statements)
references
References 24 publications
5
149
1
13
Order By: Relevance
“…Seven patients (3.7%) with history of only urban exposure to leptospires had severe pulmonary manifestations; of these, five patients died, four of them due to pulmonary hemorrhage and one due to ARDS and multiorgan failure. This study demonstrated the underdiagnosis of leptospirosis and the underrecognition of severe pulmonary involvement in this disease in a region of high endemicity [15].…”
Section: Pulmonary Involvement In Leptospirosismentioning
confidence: 75%
“…Seven patients (3.7%) with history of only urban exposure to leptospires had severe pulmonary manifestations; of these, five patients died, four of them due to pulmonary hemorrhage and one due to ARDS and multiorgan failure. This study demonstrated the underdiagnosis of leptospirosis and the underrecognition of severe pulmonary involvement in this disease in a region of high endemicity [15].…”
Section: Pulmonary Involvement In Leptospirosismentioning
confidence: 75%
“…Weil's syndrome, a severe form of this disease, is an acute febrile illness associated with multiorgan damage, including liver failure (jaundice), renal failure (nephritis), pulmonary hemorrhage, and meningitis (1), and has a 15% mortality rate if not treated (2). The molecular pathogenesis of leptospirosis is poorly understood, and the bacterial virulence factors involved are largely unknown.…”
mentioning
confidence: 99%
“…Generalmente, es leve a moderado y excepcionalmente, comanda la gravedad del cuadro. El hallazgo predominante es un compromiso hemorrágico traqueal, intersticial e intra-alveolar, que se traduce en hipoxia, insuficiencia respiratoria y en ocasiones, hemoptisis [33][34][35] . En 80 a 85% de los casos con hemoptisis la radiología de tórax demuestra infiltrados reticulo-nodulares.…”
Section: Manifestaciones Clínicasunclassified